2013
DOI: 10.1074/jbc.m112.419812
|View full text |Cite
|
Sign up to set email alerts
|

A LewisX Glycoprotein Screen Identifies the Low Density Lipoprotein Receptor-related Protein 1 (LRP1) as a Modulator of Oligodendrogenesis in Mice

Abstract: Background: LewisX is a glycan moiety expressed by neural stem cells. Results: LRP1 is a LewisX carrier protein in the mouse CNS; its deletion reduces oligodendrogenesis in the neurosphere model in vitro. Conclusion: Mouse neural stem cell lineage progression requires LRP1. Significance: This is the first study investigating LRP1 in the context of CNS development and neural stem cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 31 publications
4
39
0
Order By: Relevance
“…Our previous studies showed that LewisX glycosylated LRP1 is highly upregulated in the cortical plate (Hennen et al 2013). To investigate whether this is a unique phenomenon for the developing cortex or a more common feature of the developing CNS, we tested LRP1 and LeX expression in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies showed that LewisX glycosylated LRP1 is highly upregulated in the cortical plate (Hennen et al 2013). To investigate whether this is a unique phenomenon for the developing cortex or a more common feature of the developing CNS, we tested LRP1 and LeX expression in the spinal cord.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that cortical LRP1-deficient cells generate fewer O4-positive oligodendrocytes (Hennen et al 2013). Here we asked whether other stages of oligodendroglial development, including early PDGFRα-positive progenitors and mature MBP-positive oligodendrocytes, were also affected by the in vitro knockout.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations